M2-polarized macrophages promote metastatic behavior of Lewis lung carcinoma cells by inducing vascular endothelial growth factor-C expression (Clinics, 2012)
OBJECTIVES: Tumor-associated macrophages that generally exhibit an alternatively activated (M2) phenotype have been linked to tumor progression and metastasis. However, the role of M2-polarized macrophages in the growth and metastasis of lung adenocarcinoma remains enigmatic. The aim of this study was to explore the effect of M2 macrophages on the proliferation and migration of mouse Lewis lung carcinoma cells and tumor-induced lymphangiogenesis. METHODS: Trypan blue staining and the Transwell migration assay were performed to evaluate the effects of activated (M1 or M2) macrophages on the proliferation and migration of Lewis cells. Furthermore, vascular endothelial growth factor-C expression in Lewis cells and nitric oxide secretion from activated macrophages were detected during the co-culture assay. Following treatment with activated macrophages, lymphatic endothelial cells differentiated into capillary-like structures, and the induction of Lewis cell migration was assessed using a twodimensional Matrigel-based assay. RESULTS: In the co-culture Transwell system, the proliferation and migration of Lewis cells were promoted by M2 macrophages. Moreover, the co-culture significantly increased the expression of vascular endothelial growth factor-C by Lewis cells and reduced the secretion of nitric oxide from M2 macrophages, which subsequently led to the capillary morphogenesis of lymphatic endothelial cells. Interestingly, following co-culture with Lewis cells, the function of RAW264.7 cells was polarized toward that of the M2 macrophage phenotype. CONCLUSION: M2-polarized macrophages promoted the metastatic behavior of Lewis cells by inducing vascular endothelial growth factor-C expression. Thus, the interruption of signaling between M2 macrophages and Lewis cells may be considered to be a new therapeutic strategy.